Juvenile‐onset and adult‐onset demodicosis in dogs in the UK: prevalence and breed associations. (4th October 2019) - O'Neill, D. G.; Turgoose, E.; Church, D. B.; Brodbelt, D. C.; Hendricks, A.
Abstract : Objectives: To explore epidemiological features of demodicosis relevant to UK veterinary general practitioners. Breed risk factors were proposed as distinct between juvenile‐onset and adult‐onset disease. Materials and Methods: The study used anonymised clinical data on dogs under primary veterinary care at practices enrolled in the UK VetCompass Programme. Case inclusion required recording of a final demodicosis diagnosis for a dermatological condition that was present during the 2013 study period. Risk factor analysis used multivariable logistic regression modelling. Results: In dogs aged <2 years (juvenile‐onset), the 1‐year period prevalence was 0.48% (95% confidence interval: 0.45 to 0.52). Compared with crossbred dogs, seven breeds showed increased odds of diagnosis with demodex: British bulldog, Staffordshire bull terrier, Chinese shar‐pei, dogue de Bordeaux, pug, French bulldog and boxer. Additionally, six breeds showed reduced odds of juvenile demodicosis: Lhasa apso, bichon frise, Labrador retriever, German shepherd dog, shih‐tzu and Chihuahua. In dogs aged >4 years (adult‐onset), the 1‐year period prevalence was 0.05% (95% confidence interval: 0.0.04 to 0.06). Six breeds showed increased odds of demodicosis compared with crossbred dogs: Chinese shar‐pei, shih‐tzu, West Highland white terrier, pug, boxer and Border terrier. Clinical Significance: Juvenile‐onset demodicosis is much more common (about 10 times higher) than the adult‐onset form. Knowledge of the predisposed breeds for these two presentations can assist with diagnosis and support the concept of distinct aetiopathogenetic phenotypes.